Corruption between being and should be - Aparecido Novelli, Pedro Geraldo [UNESP]; Goretzki, Catia; Barile, Davide; Glinka, Holger; Hebing, Niklas (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2016)
Corruption is not a modern phenomenon but it has always been present in the human history. So, it is not a natural phenomenon but a historical one whose causes can be attributed to individuals as much as to political and social organizations. There is a great agreement among specialists and non-specialists about the damages and the losses that result of the practice of corruption. A common question among the ones that want to do something in order to get away with such behavior is to find the most effective way of doing it. Would there be these means? In order to give some insight for possible attitudes and plans it was asked to four philosophers, tree Germans and one Italian, if it would be viable an effective combat to corruption and what could be done. From the point of view of the researcher's common European situation and the cultural difference between two countries, it could be noticed that a solution can only go through the guiding element of the economic-social-political organization that show off corruption and its evils in the forms of privileges, marginalization and extreme poverty. More than affecting individuals, corruption strikes much more and always the collective causing abasement mainly among the least favored.
Keywords: Right; morality; ethics